DDIS-25. TARGETING GLIOBLASTOMA HETEROGENEITY WITH miR-34a. (5th November 2018) - Khan, Muhammad; Ruggieri, Rosamaria; Tran, Nhan; Sarkaria, Jann; MacDiarmid, Jennifer; Brahmbhatt, Himanshu; Boockvar, John; Symons, Marc
Abstract: microRNA-34a could serve as a novel therapeutic agent as it is under-expressed in Glioblastoma and modulates the expression of multiple genes in the deregulated p53, Rb and receptor tyrosine kinase networks which confer selective growth advantage and represent significant intra-tumoral heterogeneity, a major cause of therapeutic resistance. We studied the effects of microRNA-34a transfection in three primary patient-derived lines (GBM 6, GBM118 and GBM 126, respectively belonging to classical, mesenchymal and proneural subtypes), four established cell lines (T98G, U251, A172, LN229; where T98G and U251 show primary resistance to treatment while A172 and LN229 are sensitive) and two cell lines with acquired resistance to temozolomide (A172-TR, LN229-TR). Transfection with microRNA-34a mimics significantly reduced proliferation and sensitized to temozolomide (Combination Index< 0.2–0.6) and radiation (dose enhancement factor 1.7–2.2) treatment, regardless of baseline treatment resistance in all studied cell lines. We identified broadly conserved binding sites in the 3'UTR of multiple mRNAs in the Glioblastoma deregulated networks and genes known to confer therapeutic resistance and validated the direct downregulation of Bcl-2 protein as a major contributor to temozolomide sensitization. For in vivo delivery, nanocells (400 nm diameter), termed EDV, were derived from genetically modified bacteria, provided with a bispecific antibody targeting EGFR and loaded with microRNA-34a. EDVs were injected intravenously while temozolomide was administered by oral gavage in GBM6 orthotopic mouse model. We observed a significant reduction in tumor growth in mice treated with microRNA-34a EDV relative to control EDV-treated mice (p=0.021). Further, microRNA-34a EDV significantly improved survival and synergized with temozolomide therapy [p<0.001, median survival of control EDV, microRNA-34a EDV, control EDV with temozolomide and microRNA-34a EDV with temozolomide was 44, 48, 86 and 147+ days respectively]. In conclusion, microRNA-34a EDV is a promising novel therapeutic that inhibits Glioblastoma tumor growth and counteracts therapeutic resistance and intra-tumor heterogeneity.